Lab-on-a-chip for biology cell sorting - Mohamad Zaki Buang. (2013)
Waterborne diseases can be deadly, claiming approximately five million lives in a year globally according to statistics collated from the World Health Organisation (WHO). Pollutants in the water cause detrimental effects to not only human health but also to plants and animals. Even with preventions and measures to combat water pollution, contaminated water is being still being unknowingly consumed by a lot of people worldwide.